THE PROBLEM OF VALUES IN RUSSIAN PHILOSOPHY (XIX – BEGINNING OF XX C.): METHODOLOGICAL ASPECTS OF RESEARCH - Сколеба, І. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article considered the problem of values and human senses in the philosophical and religious studies aspects, in Russia (XIX –XX centuries).